Wind turbine blade trailing edge crack detection based on airfoil aerodynamic noise: An experimental study. (30th March 2022) - Zhang, Yanan; Avallone, Francesco; Watson, Simon
Abstract: In recent years, with the development of the wind power industry and the increase in the number of wind turbines, the condition monitoring of blades and the detection of damage are increasingly important. In this work, a new non-contact damage-detection approach is experimentally investigated based on the measurement of airfoil aerodynamic noise. A NACA 0018 airfoil with chord of 200 mm with different trailing edge crack sizes, 0.2, 0.5, 1.0 and 2.0 mm, is investigated. Experiments are conducted at different mean flow velocities, inflow turbulence intensities and angles of attack. Far-field noise scattered from the airfoil is measured by means of a microphone array. The spectral differences of sound pressure level between the damaged cases and the baseline (without any damage) are compared. As expected, at small angles of attack, with clean or low turbulence intensities (e.g. ∼ 4% in the experiment) flow, by increasing the size of the crack, tonal noise appears at trailing-edge thickness-based Strouhal number, St h, approximatively equal to 0.1. However, at higher angles of attack (e.g. ± 10° and ± 15°) or under conditions of high turbulence intensity (e.g. ∼ 7%), the amplitude of the tonal peak diminishes suggesting that complementary measurements or longer acquisition time to remove inflow turbulence effects are needed to monitor trailing edge cracks.